Analysis of Digital Fitting System Requirement in China (Journal of Fiber Bioengineering and Informatics, 2008)
Digital fitting system is a virtual fitting system based on computer and internet technology.The aim of the research, described in this paper, is to share fundamental knowledge surrounding thedevelopment of digital fitting system. In addition, we present data, collected from 1050 questionnairescompleted by both the consumers and managers in 10 cities of China, in order to analyze the requirementsfor digital fitting system in China. On this basis of this work, we conclude with some advice regarding thebuilding of digital fitting systems.
Keywords: digital fitting systems; China's apparel markets; requirement analysis; questionnaire investigation; network consumption; website quality